Analisis Kinerja Keuangan Perbankan Syariah Menggunakan Metode CAMEL di PT. Bank Tabungan Pensiunan Nasional Syariah Periode 2019-2022 - Sucipto, Moch Cahyo; Zaenal, Rian; Jalaludin, Jalaludin; Nurbaeti, Ayi (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
For banking institutions, the role of financial performance is very important. Because, if the financial performance of a bank has a good predicate, it can directly increase public confidence in making loans or investing. The fluctuating JCI in stock exchange trading certainly affects the stock performances of several issuers, including BTPN Syariah. BTPN Syariah shares have fluctuated from 2019 - 2022. And 38.77% of foreign sales have occurred, so it is very interesting to conduct this research. The purpose of this study was to determine the financial performance of Islamic banking based on the CAMEL (Capital, Asset, Management, Earning and Liquidity) method at PT. Sharia National Pension Savings Bank for the 2019-2022 Period. This study uses a descriptive method with a quantitative approach. Based on the results of the discussion above, it can be concluded that the health level of BTPN Syariah for the 2019-2022 period is based on: 1). Capital (capital) received the title "Very Healthy". Because the CAR value obtained is greater than 12% in accordance with Bank Indonesia regulations; 2). Assets (Quality of Earning Assets) received the title “Healthy”, because the KAP value obtained was below 10.35%; 3). Management (Management) by assessing the level of NPM (Net Profit Margin) gets the predicate "Sufficiently Healthy", because the NPM value obtained is in the range of 66%-81%; 4). Earning (profitability) uses two ROA and BOPO ratios, ROA for 2019-2022 gets the "Very Healthy" category, because the ROA value obtained is above 1.5%. Meanwhile, the health level of the BOPO ratio for the 2019-2022 period is in the "Very Healthy" predicate, because the BOPO value obtained is smaller than 94%. 5). Liquidity (Liquidity) using the ratio of FDR (Finance to Deposit Ratio) obtained the predicate "Sufficiently Healthy", because the FDR value obtained is in the range of 85%-100%. Furthermore, based on the results of calculating the soundness level of BTPN Syariah in 2019-2022 using the CAMEL method, it is in the "Healthy" position, because the resulting CAMEL value is in the range of 81-100, meaning that BTPN Syariah banks during the 2019-2022 period are considered capable of managing finances or performance. Islamic banking finance well.